P08.12 Insights into chlamydia trachomatis cumulative incidence in the context of widespread opportunistic chlamydia screening in england: seroprevalence study using sera from a nationally-representative household survey. (13th September 2015) - Woodhall, SC; Wills, Gillian; Horner, P; Craig, R; Mindell, JS; Murphy, G; McClure, M; Soldan, K; Nardone, A; Johnson, AM
Abstract : Introduction: The National Chlamydia Screening Programme (NCSP) was nationally implemented in England in 2008. The programme recommends that sexually-active under-25 year-olds are tested for chlamydia annually and on change of partner with the aim of interrupting transmission and preventing complications. We undertook a seroprevalence study to explore the impact of chlamydia screening on the cumulative incidence of infection up to 2012. Methods: Anonymised sera from participants in the Health Survey for England (HSE), a series of nationally-representative household surveys, were tested for anti-chlamydia antibodies using an ELISA based on the Chlamydia trachomatis -specific antigen Pgp3. Factors associated with seropositivity among 16–44 year-olds in 2010 and 2012 (years when sexual behaviour questions were included) were investigated using logistic regression. Seroprevalence trends were investigated for 1994–2012. Results: In 2010/2012, Pgp3 seroprevalence was 24% (95% CI: 22%–27%) in women and 14% (12%–16%) in men. Seroprevalence increased with age to 34% (28%–40%) in 30–34 year-old women and 20% (15%–27%) in 35–39 year-old men, and with numbers of lifetime sexual partners (17% with 1–4 partners versus 43% in those with ≥10 in women; 6% vs. 27% in men). 78% of seropositive 16–24 year-old women did not report a previous chlamydia diagnosis. Among 16–24 year-old women, there was no significant trend in seroprevalence over time and no difference in age-specific seroprevalence between birth cohorts exposed to different levels of chlamydia screening. Conclusion: In 2010–12, at least one third of women had been exposed to chlamydia by age 30–34. Most of those with evidence of previous infection did not report a previous diagnosis, presenting consequent risks of transmission and complications. A decrease in cumulative incidence among young adults following the implementation of the NCSP has not yet been demonstrated. Additional years of screening may be needed to have a measurable effect on cumulative incidence. Continued monitoring of seroprevalence is required. Disclosure of interest statement: The study was funded by the Health Protection Agency (now part of Public Health England). No pharmaceutical or diagnostic company grants were received in the development of this study.